2021
DOI: 10.1155/2021/6636894
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Layer Destruction Law of Expansive Soil Slope under Rainfall and the Application of Geogrid Reinforcement

Abstract: A large number of instability cases and laboratory tests of expansive soil slopes show that its shallow layer destruction happens because of the insufficient shear strength under the usual action of low stress and repeated dry-wet cycles. We can obtain the strength nonlinear distribution law fitted by generalized power function based on a series of shear strength tests of expansive soil considering low stress and can construct the numerical model considering the nonlinear strength distribution by FISH, to real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Geogrid reinforcement is an example of a flexible limitation measure, which can inhibit the displacement generated by moisture absorption of expansive soil slopes and allow a moderate amount of deformation [127,128]. Small geogrid mesh sizes are recommended, providing better slope reinforcement [129]. Some scholars have used geo-cells flexible retaining walls to effectively limit swelling-shrinkage deformation of expansive soil slopes [130].…”
Section: Limitation Of Swelling-shrinkage Deformationmentioning
confidence: 99%
“…Geogrid reinforcement is an example of a flexible limitation measure, which can inhibit the displacement generated by moisture absorption of expansive soil slopes and allow a moderate amount of deformation [127,128]. Small geogrid mesh sizes are recommended, providing better slope reinforcement [129]. Some scholars have used geo-cells flexible retaining walls to effectively limit swelling-shrinkage deformation of expansive soil slopes [130].…”
Section: Limitation Of Swelling-shrinkage Deformationmentioning
confidence: 99%
“…In order to reduce the occurrence of expansive soil slope disasters, geogrid reinforcement, a technology of "soft swelling", is widely used in engineering. Moreover its technical effectiveness, economic and environmental protection have been proved and verified by a large number of practices [3][4][5][6][7][8] . Research on this block mainly focuses on mechanics, while the research on cracks is rarely found, so it is necessary to study.…”
Section: And Wang Guiyaomentioning
confidence: 99%
“…It is important to note that the geogrid reinforcement spacing exerts a notable influence on the stability of expansive soil slopes. e smaller the reinforcement spacing is, the higher the slope stability [82].…”
Section: Flexible Supportmentioning
confidence: 99%